Beban Alternator Fasa Tiga Simulasi Dalam Laboratorium - Yuwono, Teguh (Universitas Diponegoro, 2006)
Abstract Â Electrics usage by consumer according to its requirement. Burden of electrics usage by assorted consumer, but the conclusion burden of electrics usage is have the character of the resistive, capacitive and inductive. Physicly in the form of resistor, inductor, and capacitor. Burden in electrics usage not stand-alone but became to one union of network of requirement of usage electrics energy. In electrics three phasa, burden can be linked by a star or delta, at same burden linked by a star or delta will permeate the same electrics energy but differing at current ampere and voltage. Â Keyword: resistor; inductor; capacitor; star and delta connection.